Solid state, dry zinc/MCM-41/air cell as relative humidity sensor - Saputra, Hens; Othman, Raihan; Sutjipto, Agus Geter Edy; Muhida, Riza; Ani, Mohd Hanafi (Elsevier, 2012)
A zinc–air cell utilizing an inorganic MCM-41 membrane separator, in its dry form, reveals a unique behavior in response to relative humidity variation. The open circuit voltage (OCV) of the cell shows a linear dependence on relative humidity content. This is due to water adsorption–desorption characteristics of the mesoporous MCM-41 material. Comparison between relative humidity data obtained from commercial digital humidity sensor with data deduced from the OCV readings of Zn/MCM-41/air cell shows good sensitivity and high reliability.